1998
DOI: 10.1203/00006450-199806000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Moderate Hypothermia after Neonatal Hypoxia-Ischemia: Short- and Long-Term Outcome

Abstract: We have previously shown that mild hypothermia applied after hypoxia-ischemia in newborn piglets and rats reduces brain injury evaluated 3-7 d after the insult. The aim of the present study was to assess the neuroprotective efficacy of hypothermia with respect to short- (neuropathology) and long-term (neuropathology and sensorimotor function) outcome after hypoxia-ischemia in 7-d-old rats. One hundred fourteen animals from 13 litters survived either 1 or 6 wk after a hypoxic-ischemic insult. The animals were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
232
4
4

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 315 publications
(258 citation statements)
references
References 31 publications
12
232
4
4
Order By: Relevance
“…The improvement of long-term motor behavior after hypothermia was also demonstrated in a rat model of neonatal HI (4). To date, gender effects of hypothermia were reported only by Bona et al (15), who observed more effective neuroprotection in female rats than in male rats. In the present study, we observed strong neuroprotective effects of hypothermia in female rats but saw weaker effects in male rats.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The improvement of long-term motor behavior after hypothermia was also demonstrated in a rat model of neonatal HI (4). To date, gender effects of hypothermia were reported only by Bona et al (15), who observed more effective neuroprotection in female rats than in male rats. In the present study, we observed strong neuroprotective effects of hypothermia in female rats but saw weaker effects in male rats.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, EPO treatment of perinatally asphyxiated human term neonates has also proven to be beneficial (14). In recent studies with a rodent model, females appear to benefit more from neuroprotective interventions after HI, such as hypothermia, EPO, and 2-iminobiotin (15)(16)(17).…”
mentioning
confidence: 99%
“…This leads to the question of how to transfer 'time' in a rat model to larger animal models and to humans. With our neonatal HT research that led to effective clinical trial outcome, we found in the rat that 51C to 61C cooling for 3 h (Thoresen et al, 1996b) or 5 h (Bona et al, 1998) was protective, in the pig 24 h of HT (combined selective head cooling and body cooling by 4.51C) was neuroprotective, in the sheep 76 h cooling was effective even after a delayed start of 5.5 h (Gunn et al, 1998), and in humans 72 h of 3.51C cooling was neuroprotective (Gluckman et al, 2005;Shankaran et al, 2005) in clinical trials where cooling on average started 4.5 h after birth.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothermic protection was further confirmed in newborn pigs (2-3,36) and fetal sheep (4,37) before successful clinical trials of therapeutic HT (5-7). For the postnatal day 7 rat model to show long-term neuroprotection, at least 3 h of 5 °C reduction in core temperature is needed (31)(32)(33)38). We reduced experimental variability by brief duration of anesthesia (median 5.5 min; two experienced researchers performing ligations in parallel), short duration (<180 min) between carotid ligation and the beginning of hypoxia, and tightly controlled temperature, oxygen, and CO 2 levels in our specially designed exposure chamber (32).…”
Section: Methodsmentioning
confidence: 99%